Failures in Transition: Learning from Incidents Relating to Clinical Handover in Acute Care. Issue 3 (23rd January 2012) - Thomas, Matthew J.W.; Schultz, Timothy J.; Hannaford, Natalie; Runciman, William B.
Abstract The appropriate handover of patients, whereby responsibility and accountability of care is transferred between healthcare providers, is a critical component of quality healthcare delivery. This paper examines data from recent incidents relating to clinical handover in acute care settings, in order to provide a basis for the design and implementation of preventive and corrective strategies. A sample of incidents (n = 459) relating to clinical handover was extracted from an Australian health service's incident reporting system using a manual search function. Incident narratives were subjected to classification according to the system safety and quality concepts of failure type, error type, and failure detection mechanism. The most prevalent failure types associated with clinical handover were those relating to the transfer of patients without adequate handover 28.8% (n = 132), omissions of critical information about the patient's condition 19.2% (n = 88), and omissions of critical information about the patient's care plan during the handover process 14.2% (n = 65). The most prevalent failure detection mechanisms were those of expectation mismatch 35.7% (n = 174), clinical mismatch 26.9% (n = 127), and mismatch with other documentation 24.0% (n = 117). The findings suggest the need for a structured approach to handover with a recording of standardized sets of information to ensure that critical components are not omitted. Limitations of existing reporting processes are also highlighted.